A review on activated carbon modifications for the treatment of wastewater containing anionic dyes. (November 2022) - Azam, Kshaf; Shezad, Nasir; Shafiq, Iqrash; Akhter, Parveen; Akhtar, Farid; Jamil, Farrukh; Shafique, Sumeer; Park, Young-Kwon; Hussain, Murid
Abstract: Polluted water resources, particularly those polluted with industrial effluents' dyes, are carcinogenic and hence pose a severe threat to sustainable and longstanding worldwide development. Meanwhile, adsorption is a promising process for polluted/wastewater treatment. In particular, activated carbon (AC) is popular among various wastewater treatment adsorbents, especially in the organic contaminants' remediation in wastewater. Hence, the AC's synthesis from degradable and non-degradable resources, the carbon activation involved in the AC synthesis, and the AC's modification to cutting-edge and effective materials have been modern-research targets in recent years. Likewise, the main research focuses worldwide have been the salient AC characteristics, such as its surface chemistry, porosity, and enhanced surface area. Notably, various modified-AC synthesis methods have been employed to enhance the AC's potential for improved contaminants-removal. Hence, we critically analyze the different modified ACs (with enhanced (surface) functional groups and textural properties) of their capacity to remove different-natured anionic dyes in wastewater. We also discuss the corresponding AC modification techniques, the factors affecting the AC properties, and the modifying agents' influence on the AC's morphological/adsorptive properties. Finally, the AC research of future interest has been proposed by identifying the current AC research gaps, especially related to the AC's application in wastewater treatment. Graphical abstract: Image 1 Highlights: Dye-polluted wastewater is carcinogenic. AC-based adsorption is a promising process for dye-polluted wastewater treatment. AC's surface chemistry, porosity, and enhanced surface area are reviewed in detail. AC modification techniques, tuning factors, and the modifying agents' are reviewed. Research gaps in the application of AC in wastewater treatment are furnished.